Pengaruh Transparansi, Akuntabilitas, dan Sistem Pengendalian Internal Terhadap Kinerja Keuangan Pemerintah Daerah: Studi Kasus di Badan Pengelola Keuangan dan asset Daerah Kota Tidore Kepulauan - Jainuddin, Sitna; Gaffar; Mattoasi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the influence of transparency, accountability, and internal control system on the financial performance of regional government. This study uses a quantitative and total sampling technique for data collection. The data analysis technique is descriptive quantitative analysis, utilizing t statistics, f statistics, and the coefficient of determination (adjusted R Square) though IBM SPSS 20 for windows. The result shoe that transparency positively and significantly influences the regional government’s financial performance. Similarly, accountability also positively and significantly influences the regional government’s financial performance. Furthermore, internal control systems positively and significantly influence the regional government’s financial performance as well. Simultaneously, transparency, accountability, and internal control system positively and significantly influence the regional government’s financial performance, with a determinant value of 60,7%, while the remaining 30,3% is due to other factors that are not examined in thid study.